Inventory of Medicinal Plants in the Ethnobotanical Traditions of the West Sumatran Community - Filza Yulina Ade; Fadilaturahmah Fadilaturahmah; Rahmi Kurniati (Jurnal Penelitian Pendidikan IPA, 2025)
This study analyzes the ethnobotanical utilization of medicinal plants in West Sumatra based on the traditional Minangkabau territorial systems (Darek, Rantau, and Pesisir) and examines its implications for contextual science education. A mixed descriptive–quantitative ethnobotanical approach was employed involving 240 key informants (105 from Darek, 90 from Rantau, and 45 from Pesisir) selected through purposive and snowball sampling. Data were collected using structured interviews, participatory observation, and species documentation. Quantitative ethnobotanical indices, including Use Value (UV) and Fidelity Level (FL), were applied. The results identified 38 medicinal plant species from 24 families. Curcuma longa (UV=0.88), Zingiber officinale (UV=0.84), and Tinospora crispa (UV=0.81) were the most culturally important species. High FL values were observed for Andrographis paniculata in fever treatment (92.1%) and Curcuma longa for digestive disorders (89.6%), indicating strong cultural reliability. The findings demonstrate that Minangkabau ethnobotanical knowledge is territorially structured, culturally transmitted, and empirically reliable. This study provides a scientific foundation for the development of ethnoscience-based science learning resources, supporting contextual learning, scientific literacy, and cultural preservation in Indonesian secondary education